AVIAN SYMBOLISM AND CULTURAL MEMORY: EXPLORING BIODIVERSITY AND URBANIZATION IN TURKISH AND AMERICAN LITERATURE - İbrahim Koç (Toplum ve Kültür Araştırmaları Dergisi)
This article aims to examine one of the key principles of environmental philosophy, the direct relationship between cultural memory and biodiversity, in the context of three literary works selected from Turkish and American literature. These works trace a process of change in cultural texture due to rapid urbanization and population growth, as well as social transformations experienced just before and after rapid industrialization periods. Another common point is that all three of them deal with different aspects of bird hunting. Bird symbolism has been used effectively to highlight the contrast between rural and urban cultures. In addition to these symbolic relationships based on the natural characteristics of the birds, these texts use different aspects of avian life to interpret multiple layers of meaning, enriched by intercultural and intracultural references provided by history and tradition. It should be underlined that these fictional narratives, which sometimes use the natural environment for allegorical purposes, do not have didactic qualities. These ecocentric texts use birds not only in their traditional symbolic meaning, but also, either as a character or a theme, as real beings. By establishing a direct relationship between urbanization and reduction of biodiversity, inseparable role of birds in the cycles of nature, of which human beings are also a part, is emphasized. Finally, in this study, besides their cultural and historical importance, contribution of birds to the sustainability of biodiversity is discussed through the following literary works: Two of them, 'The Last Birds' and The Birds Have Also Gone, compare the value judgments and lifestyles of Istanbul’s pre-industrial urban era with the post-industrial situation. The last one, ‘A White Heron’, focuses on the relationship between rural life experiences and environmental awareness. This comparison leads to the conclusion that industrial urban life poses a significant obstacle to appreciating the intrinsic value of nature.